The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1099/mic.0.052571-0
|View full text |Cite
|
Sign up to set email alerts
|

Target recognition, resistance, immunity and genome mining of class II bacteriocins from Gram-positive bacteria

Abstract: Due to their very potent antimicrobial activity against diverse food-spoiling bacteria and pathogens and their favourable biochemical properties, peptide bacteriocins from Gram-positive bacteria have long been considered promising for applications in food preservation or medical treatment. To take advantage of bacteriocins in different applications, it is crucial to have detailed knowledge on the molecular mechanisms by which these peptides recognize and kill target cells, how producer cells protect themselves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
94
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(98 citation statements)
references
References 87 publications
1
94
0
2
Order By: Relevance
“…In S. mutans, several class II bacteriocins are expressed through the CSP-ComDE quorum-sensing system (16,26,48). Class II bacteriocins are antimicrobial peptides that function to kill competitors by dissipating the proton motive force via pore formation in the cytoplasmic membrane of target cells (23). Interestingly, preliminary work done in our lab demonstrated that inactivation of mutacin V (CipB), but not mutacin IV (NlmAB), completely abolished the increase in persister numbers observed for the WT strain following pretreatment with the CSP pheromone.…”
Section: Discussionmentioning
confidence: 99%
“…In S. mutans, several class II bacteriocins are expressed through the CSP-ComDE quorum-sensing system (16,26,48). Class II bacteriocins are antimicrobial peptides that function to kill competitors by dissipating the proton motive force via pore formation in the cytoplasmic membrane of target cells (23). Interestingly, preliminary work done in our lab demonstrated that inactivation of mutacin V (CipB), but not mutacin IV (NlmAB), completely abolished the increase in persister numbers observed for the WT strain following pretreatment with the CSP pheromone.…”
Section: Discussionmentioning
confidence: 99%
“…The immunity proteins do not prevent the formation of bacteriocin-receptor complex by binding to the receptors competitively. (Kjos et al 2011). As a side effect, glucose transport is also blocked, leading to the reduced growth on glucose.…”
Section: ) As Hydrophobic Interactions Are Normally Involved In mentioning
confidence: 99%
“…In immune cells (b), the bacteriocin mediates the same conformational changes, but the pore is blocked by a specific immunity protein (dark blue) which tightly binds to EII t Man -bacteriocin complex. Adapted from Kjos et al (2011).…”
Section: ) As Hydrophobic Interactions Are Normally Involved In mentioning
confidence: 99%
See 1 more Smart Citation
“…Bacteriocins are found in both Gram-positive and Gram-negative bacteria, and together, they constitute a large and diverse group of antimicrobial peptides and proteins. Within the Gram-positive bacteria, particularly LAB, bacteriocins are found abundantly and have been extensively studied with respect to structure, diversity, mode of action, production, and target specificity (5). Bacteriocins have been divided into three classes: class I, lantibiotics, which are small and heavily modified peptides containing lanthionine residues; class II, unmodified bacteriocins, which are small, unmodified peptides or peptides with minor modifications (such as sulfide bridges); and class III, lytic and relatively large proteins (6).…”
Section: Importancementioning
confidence: 99%